Forestry solutions for mitigating climate change in China - Gao, Guanglei; Ding, Guodong; Zhao, Yuanyuan; Bao, Yanfeng; Yu, Minghan (Forest Systems, 2014)
Aim of study: Forests have vital functions in global carbon cycle, and thus are of prime importance in efforts to curb climate change. This study intends to guide effective forestry solutions to combat climate change in China. Area of study: China, not only a major emitter of greenhouse gases, but also one of the five most-forest richest countries with the largest plantations in the world. Material and methods: We summarize and recommend carbon sequestration forestry by considering two Kyoto Protocol activities: afforestation/reforestation and forest management. Main results: Afforestation has a top priority of carbon sequestration forestry in China. However, the tree-based solution will reach its limits to growth in a predictable near future. Forest management contributes to break the deadlock. When scientifically and sustainably managed, forests still have a central role in climate change mitigation. Research highlights: China’s efforts on carbon sequestration forestry should shift the focus from afforestation to forest management. Key words: climate change; carbon sequestration forestry; afforestation; forest management.